Branching-Time Model-Checking of Probabilistic Pushdown Automata. - Brázdil, T; Brozek, V; Forejt, V (2009)
In this paper we study complexity of the model-checking problem for probabilistic pushdown automata (pPDA) and qualitative fragments of two branching-time logics PCTL* and PECTL*. We prove tha this problem is in 2-EXPTIME for pPDA and qualitative PCTL*. Consequently, we prove that model-checking of stateless pPDA (pBPA) and both qualitative PCTL* and qualitative PECTL* is 2-EXPTIME-hard. These results combined with results of several other papers give us that the model-checking problem for pPDA (and also for pBPA) and both qualitative PCTL* and qualitative PECTL* is 2-EXPTIME-complete. Finally, we survey known results on model-checking of pPDA and branching-time logics. © 2009 Elsevier B.V. All rights reserved.